2020
DOI: 10.3390/met10101286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manufacturing Conditions on Inclusion Characteristics and Mechanical Properties of FeCrNiMnCo Alloy

Abstract: Three CoCrFeMnNi high-entropy alloys (HEAs) were produced by vacuum induction melting, induction melting under inert gas atmosphere, and melting under inert gas atmosphere followed by air exposure, respectively. The different manufacturing conditions for the three investigated alloys resulted in different levels and types of inclusions. The alloys melted under vacuum or inert gas contained Al2O3 inclusions formed by impurity Al, due to its high oxidation tendency. The molten alloy exposed in air showed an exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 60 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…However, since the volumetric fraction of these impurities was less than 1% according to Table 1, the corresponding XRD spectrum (Figure 2) has possibly not shown its presence. As emphasized in [29,32], non-metallic inclusions could be found EM mapping of the cross-section of the dendrites is presented in Figure 4. The transversal size of the dendrites is 7.7 ± 0.4 µm, which confirms the results of the optical microscopy.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, since the volumetric fraction of these impurities was less than 1% according to Table 1, the corresponding XRD spectrum (Figure 2) has possibly not shown its presence. As emphasized in [29,32], non-metallic inclusions could be found EM mapping of the cross-section of the dendrites is presented in Figure 4. The transversal size of the dendrites is 7.7 ± 0.4 µm, which confirms the results of the optical microscopy.…”
Section: Resultsmentioning
confidence: 85%
“…However, since the volumetric fraction of these impurities was less than 1% according to Table 1, the corresponding XRD spectrum (Figure 2) has possibly not shown its presence. As emphasized in [29,32], non-metallic inclusions could be found even in the equiatomic FeCrNiMnCo alloys melted under vacuum or using an inert gas atmosphere. For example, Al 2 O 3 inclusions can be formed due to the high affinity between aluminum and oxygen, which were observed in an FeCrNiMnCo alloy [33].…”
Section: Resultsmentioning
confidence: 86%
“…Previous studies demonstrated that the chemical composition and routes of their formation strongly influence the microstructure and subsequent physical and mechanical behavior [1]. There are various methods of fabrication of bulk HEAs: vacuum arc melting [2], vacuum induction melting [3], selective laser melting [4] and additive manufacturing methods such as wire-arc additive manufacturing [5] and laser cladding [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many HEAs. such as FeCoCrNiMn and AlCoCrFeNi, were developed based on FeCoCrNi [26][27][28]. In this study, FeCoCrNi HEAp was used as a reinforcement to prepare AMCs.…”
Section: Introductionmentioning
confidence: 99%